An Analysis of Themes In “The Magic” And Its Indonesian Translation (A Systemic Functional Grammar Approach) - Dewi Riani (Universitas Pendidikan Indonesia (UPI), 2015)
The present study entitled An Analysis of Themes in “The Magic”and Its Indonesian Translation (A Systemic Functional Grammar Approach) aims to find out the types of Theme in the original version and the translated version of The Magic, and Themes realization in the Indonesian translated version. This study employed a descriptive qualitative method. The present study adopted Halliday’s (1994) theory of Systemic Functional Grammar as a tool of analysis to analyze the Themes used in the texts, and Eggins’ (2004) theory of thematic progression. The study finds three types of Theme both in the source and in the target text; Topical Theme, Textual Theme and Interpersonal Theme. The study also finds four patterns of Theme realization in the Indonesian translation of The Magic. The first pattern the Themes are translated like the original. The second pattern, part of the Theme is ellipted. The third pattern, there are some words from Rheme translated as Theme. The last, the Themes are shifted in the process of translationKeywords: Theme, Rheme, Translation, Systemic Functional Grammar